Concrete, masonry, and wood foundation walls - International Code Council ([Illinois] : International Code Council, 2003)
This program discuss the provisions for concrete, masonry, and wood foundation walls generally associated with conventional light-frame construction methods. Various methods of foundation wall construction are addressed in this program
Title from title screen
Title on workbook: IRC 2000/2003 workbook: concrete, masonry and wood foundation walls
DVD format
Keywords: Foundations; Concrete footings